The cooperation between orf virus and Staphylococcus aureus leads to intractable lesions in skin infection - Yu, Yongzhong; Cui, Yudong; Song, Baifen (Frontiers in Cellular and Infection Microbiology, 2024)
A large amount of evidence shows that different kinds of microorganisms can jointly cope with environmental pressures including cell hosts. For example, in many cases, it has been found that secondary or mixed infection of animals caused by ORFV (an epitheliophilic Parapoxvirus) and bacteria (such as Staphylococcus aureus or Streptococcus) shows a mutual aid mode that indirectly leads to the deterioration of the disease. However, the lack of research on the co-pathogenic mechanism, including how to hijack and destroy the cell host in the pathological microenvironment, has hindered the in-depth understanding of the pathogenic process and consequences of this complex infection and the development of clinical treatment methods. Here, we summarized the current strategies of trapping cell hosts together, based on the previously defined ORFV-Host (O-H) system. The opportunistic invasion of S. aureus destroyed the delicate dynamic balance of the O-H, thus aggravating tissue damage through bacterial products (mediated by Agr), even causing sepsis or inducing cytokine storms. In fact, the virus products from its adaptive regulatory system (VARS) weaken the immune attacks and block molecular pathways, so that S. aureus can settle there more smoothly, and the toxins can penetrate into local tissues more quickly. This paper focuses on the main challenges faced by cell hosts in dealing with mixed infection, which provides a starting point for us to deal with this disease in the future.